Two Novel Short Peptidoglycan Recognition Proteins (PGRPs) From the Deep Sea Vesicomyidae Clam Archivesica packardana: Identification, Recombinant Expression and Bioactivity - Kong, Xue; Liu, Helu; Li, Yanan; Zhang, Haibin (Frontiers in Physiology, 2018)
Vesicomyidae clams are common species living in cold seeps, which incorporates symbiotic bacteria into their body maintaining endosymbiosis relationship. As members of pattern recognition receptor (PRR) family, peptidoglycan recognition proteins (PGRPs) recognize pathogen associated molecular patterns and play an important role in innate immunity. In present study, two short PGRPs (ApPGRP-1 and -2) were first identified from Vesicomyidae clam Archivesica packardana. Sequences analysis showed that they have both conserved Zn2+ binding sites (H-H-C) and amidase catalytic sites (H-Y-H-T-C), and phylogenetic tree indicated that they clustered with short PGRPs of other molluscs. PGN assay showed that ApPGRPs could bind Lys-type PGN from Staphylococcus aureus and Dap-type PGN from Bacillus subtilis, and revealed amidase activity with selective zinc ion dependence. rApPGRP-1 and -2 (recombinant ApPGRP-1 and -2) could bind six bacteria with a broad spectrum and had both zinc-dependent and -independent bactericidal activity. ApPGRPs had the complete functions of effectors and partial functions of receptors from PGRPs. Further analyses showed that ApPGRPs from A. packardana might be involved in the endosymbiosis relationship between the host clam and endosymbiotic bacteria as a regulator. The results of these experiments suggested that ApPGRPs were involved in cold seep clams’ immune response. This study provides basic information for further research on the immune mechanisms of deep sea organisms.